Tell Abu al-Kharaz in the Jordan Valley Volume III: The Iron Age - Fischer, Peter M. (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
Tell city of Abu al-Kharaz is situated in the central Transjordanian Jordan Valley and excavated by the author from 1989 to 2012. The town flourished in the Early Bronze Age, and after an occupational lacuna of more than thousand years the site was re-occupied in the second half of the Middle Bronze Age and remained permanently occupied until the end of the Iron Age. The new volume is No. III in a series of three (The Early Bronze Age Vol. I, published by the Austrian Academy of Sciences Press in 2008, and the Middle and Late Bronze Ages Vol. II, in 2006).